Quality medical care for adolescents: adolescents versus physiciansâ perception - Madalena Meira Nisa; Antonio Videira-Silva; Mariana Beatriz Fonseca Mourasup; Sofia Moeda; Sílvia Freira; Helena Fonseca (Portuguese Journal of Pediatrics)
Introduction and Objectives: Adolescence is a key developmental period, requiring a distinct clinical approach. Aspects such as communication, confidentiality, and privacy are particularly relevant in adolescence, as indicators of the quality of health care according to the World Health Organization. This study aimed to assess the quality of health care provided to adolescents in a tertiary hospital, based on adolescents’ and physicians’ perspectives. Method: Adolescents attending the outpatient clinic and physicians who may regularly see adolescents in consultation (including pediatricians and other specialties) were invited to participate. Two content-matched questionnaires assessing medical care for adolescents were applied to both groups. Results: A total of 112 adolescents and 80 physicians participated. Most adolescents felt empathy with the doctor (98.1%), felt involved in therapeutic decisions (90.7%), and reported spending time alone with the doctor during the consultation (85.9%). Almost all physicians (98.8%) reported showing an empathetic attitude towards gender identity, sexual orientation, ethnicity, and religion and reported that they managed to establish a therapeutic relationship with the adolescents. There was a tendency for non-pediatricians to report a greater interest in seeing adolescents compared to pediatricians (Md = 4/5 versus Md = 3/5; p = 0.057). Most physicians (81.3%), but a minority of adolescents (37.1%), perceived that the concept of confidentiality was explained during the appointment (p < 0.001). Discussion: There seems to be a growing awareness in the medical community of the emergent need for differentiated care in adolescence. Yet, topics such as confidentiality still require improvement, which highlights the need to invest in medical training in this area, even among pediatricians.